The problem of the definition of abortion in Polish literature and reception of church teaching in this regard - Biały, Stanisław (Kwartalnik Naukowy Fides et Ratio, 2022)
The topic of abortion is still relevant in the social discourse. Therefore, the author analyzed the conceptualisation of the act of abortion (present in Polish literature), conducted a questionnaire to confirm or exclude the obtained theoretical results, and asked about possible causes of such a phenomenon. Research shows that the Catholic Church has presented the doctrinal concept of abortion (precisely enough) in such documents as Qauesito de abortu procurato, Donum vitae, Evangelium vitae, and Dignitas personae. However, its definition (in terms of the subject matter) quite often differs from that found in various publications or statements referring to the Magisterium of the Church. This is a harmful situation, which may translate into a difficult reception of the Church’s teaching, as well as into respect for innocent human life. The point is that if the cognitive process is characterized by “intentionality” (the relation of the mind to the object), its objectivity may be hindered by volitional, ideological, conscious, contextual acts, etc. goals by oneself: scientific, political, ideological, social, moral, canonical, etc.